Pengaruh Diferensiasi Produk terhadap Keputusan Pembelian Coca-Cola di Wilayah Pekanbaru - Sari, Efti Novita; Jufri, Muhammad (Jurnal Bisnis dan Pemasaran Digital, 2022)
Purpose: To determine simultaneously and partially the effect of product differentiation (product design, brand, packaging, size, and taste) on purchasing decisions for Coca-Cola in Pekanbaru. Method: Data collection techniques using a questionnaire comprising 25 statement items for product differentiation variables and 5 statement items for product purchase decision variables were distributed to 50 consumers who consumed Coca-Cola products. Results: Based on the results of this study, it is known that simultaneously and partially there is a significant influence of product differentiation (product design, brand, packaging, size, and taste) on purchasing decisions for Coca-Cola in the Pekanbaru area. The research results were 36.20%. Limitations: This research was conducted only on Coca-Cola products. These variables include product design, brand, packaging, size, taste, and their influence on purchase decisions for Coca-Cola products. Contribution: Suggestions can be given to PT Coca-Cola to continue to improve and develop innovations in all aspects of marketing, because Coca-Cola products have been well trusted by all circles of society, and further increase consumer loyalty to Coca-Cola products by providing optimal service and product innovation based on consumer needs, in order to increase consumer purchasing decisions for Coca-Cola products.